Noragami : stray god. 17 - Adachi, Toka (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2016)
The battle inrensifies as Bishamon approaches the crafter. Kazuma and her other shinki are spared divine retribution, but Kazuma will stop at nothing to save his master from punishment. Meanwhile, Yato faces Takemikazuchi in an attempt to reason with the Heavens."--Back cover.